The Significance of Nahj-ul-Balaghah in the Development of Muslim Theosophy: An Analytical Exposition (Al-Qamar, 2025)
Nahj ul Balagah, the seminal work of wisdom by Ali ibn Talib (Karm Allah Wajho)[i] comprises the sermons, letters and sayings, delivered by him on various occasions during his life till his death. Every piece of writing in this work is exponent of his wisdom and his scholarship. The objective of this article is to highlight the role of Hazrat Ali’s insight and wisdom in the history of theology and theosophy of Islamic history of thought. Moreover, the focus of this humble research is to bring into light the missing aspect of Hazrat Ali’s personality as Theologian and Theosophist along-with to reveal the significance of his sermons and saying in the hot debates of that time theological sects and schools of thought. All his sermons, sayings and letters had been collected (Sharif al-Radi, 970 –1015 AD) and named as Nahj ul Balagah. This book has been read, quoted and revered but it is tragic fact that it had neither been given proper place nor understood impartially. In the same manner, the author, Hazrat Ali (KAW) had been respected and remembered as valor, wise, generous and pious person but very little had been mentioned regarding his being as a Theologian and Theosophist. This research article would reveal the significance of this book, and its relevance regarding the theological or theosophical dimension of the problem of Muslim Theology and Theosophy.
Keywords: Illah’yat; Attributes; creatio ex nihilo; Ilm-ul-Kalam; Metaphysics; Muslim Philosophy; Theology; Theosophy; Wisdom